Current Updates of Biomaterials for Skin Replacement: A Systematic Review - Normalina Sandora; Nur Amalina Fitria; Aditya Wardhana; Nandita Melati Putri; Akhmad Noviandi Syarif; Tyas Rahmah Kusuma; Benati Karimah (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2025)
Background: The human skin envelops the entire body surface and is highly susceptible to damage. Partial- and full-thickness skin loss often necessitates the use of skin substitutes. Autologous grafting remains the gold standard for skin replacement. Furthermore, the application is usually constrained by the limited availability of donor skin, the technical challenges of surgery, and the added difficulties encountered in severe cases. In this systematic review, we summarise the strengths and limitations of biological and synthetic biomaterials as skin substitutes, with evidence drawn from clinical practice, human trials, and preclinical animal studies. This systematic review evaluates the advantages and disadvantages of biological and synthetic biomaterials used as skin substitutes, drawing evidence from clinical practice, human studies, and animal studies.”Method: We performed a comprehensive literature review using the search engines OVID, ScienceDirect, Google Scholar, and PubMed databases. Search terms or keywords included